IMPACT OF TECHNICAL EDUCATION POLICY AMENDMENT: NEP 2020 - Pandya, Ghanshyam T.; Singh, Nikhil Kumar; Parikh, Sachin P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
An all-encompassing reform, the National Education Policy (NEP) 2020 seeks to revolutionize India’s educational system. Development in all areas, including critical thinking and the acquisition of skills at a young age, are prioritized. NEP promotes flexibility in learning pathways, integration of arts and sciences, and technology-driven education. Its goals include encouraging research and innovation, raising awareness of the value of bilingualism, and improving the standard of education. NEP is in favor of rethinking teacher preparation programs, giving schools more freedom to operate as they see fit, and putting more emphasis on vocational education. In sum, the overarching goal of NEP 2020 is to build a school system that is both welcoming and equipped to meet the challenges of the twenty-first century. A new approach to education that emphasizes the development of well-rounded skills is promised by the National Education Policy (NEP) 2020 for technical education. Emphasizing critical thinking and creativity, it advocates for learner-centered approaches and integration of technology. NEP aims to empower students by offering flexibility in learning paths and promoting multidisciplinary education. For faculty, it offers continuous training opportunities and career advancement mechanisms. NEP also aligns vocational education with industry demands, fosters research and innovation, and enhances institutional autonomy. By addressing equity concerns and promoting international collaboration, NEP 2020 seeks to create a robust and inclusive educational ecosystem for India’s future. Research in this area looks at how various players in the technical education sector have fared as a result of NEP 2020. It explores the many ways in which NEP 2020 affects Academics, Students, Faculties, Employment, Research, and Institutes, illuminating the complex effects and consequences for all of these important groups.